Microsatellite molecular marker-assisted gene pyramiding for resistance to Asian soybean rust (ASR) - Viganó, Joselaine (2018)
The present study aimed at pyramiding ASR-resistance genes through microsatellite (SSR) marker-assisted selection (MAS) and demonstrating the pyramiding steps. To obtain the first generation of gene pyramiding, crosses were made between introduced plants (PI’s), which have the genes Rpp1, Rpp2, Rpp3, Rpp4, and Rpp5. F1 plants from the initial crosses were intercrossed to obtain plants with the four resistance genes (second pyramiding generation). Plants selected from this second generation were again intercrossed (third pyramiding generation) to increase the number of pyramided genes. For MAS, we used informative SSR markers in each cross. SSR markers were considered informative when the source resistance allele containing the target gene could be followed in the progeny, even in crosses between hybrids that both contained the same allele. Markers published in the ASR genetic mapping studies and in the consensus map of the soybean were used. We obtained plants containing from 2 to 4 genes pyramided per plant. These plants can be used as a source of multiple resistance in breeding programmes for obtaining soybean varieties with more durable resistance to ASR.